Theoretical foundations of industrial policy - Elie Cohen (EIB Papers, 2006)
Highlighting the revival of industrial-policy thinking in an era of globalisation and disenchantment with free trade, this paper reviews alternative and, in part, competing theoretical foundations of industrial policy: neoclassical foundations, structuralist approaches, and pragmatic approaches inspired by new growth and development theories. One of the main conclusions is that the industrial-policy debate is no longer between advocates of horizontal and vertical policies, but between those who deny any potential for state intervention to make economies more dynamic and those who seek to clarify the specific conditions for appropriate intervention. Another salient conclusion is that state intervention is especially important in a knowledge-based economy, as witnessed by successful industrial policies in - for instance - the United States, Germany and France, and Finland.
Keywords: 330; Industriepolitik; Theorie; Deutschland; Frankreich; Finnland; USA